Paraoxonase activity assessment in dogs suffering from Parvovirus infection - SALARPOUR, R.; AHMADMAHMUDI, M. ZAMANI; REZAEI, M.; ESKANDARZADE, N. (Journal of the Hellenic Veterinary Medical Society, 2021)
Canine Parvovirus enteritis is one of the most common causes of diarrhea and death in dogs younger than 6 months of age. Clinical gastroenteritis in parvo-positive dogs is associated with increased levels of lipid peroxides and alteration in antioxidant enzymes. Paraoxonase/arylesterase 1 is considered as an antioxidant enzyme and acute phase protein in laboratory animals and human. The present study evaluated paraoxonase activity in 27 dogs suffering from Parvovirus infection and compared with 9 normal dogs. Blood samples were taken from all of the dogs and were sent to the laboratory for complete cell blood count and also biochemical factors assessment (paraoxonase/arylesterase 1 activity, liver, kidney and metabolic profiles). Infected dogs significantly showed decrease in paraoxonase/arylesterase 1 enzyme activity, an increase number of neutrophils and lymphopenia compared with parvo-negative dogs. Significant decrease in the enzyme activity was also observed in dogs with neutropenia or leukocytosis when compared to control group. It seems that in dogs paraoxonase/arylesterase 1 enzyme activity is decreased as a part of acute phase response in Parvovirus infection.